CORONA VIRUS IN DEVELOPING COUNTRIES - Alsabunchi , A.; Alsabunchi , O. (EurasianUnionScientists, 2021)
Developing countries now account for three-quarters of the 100,000 daily new coronavirus cases that authorities around the world are reporting. The steady rise is alarming, according to the World Health Organization, as many epidemiologists say they think the figures are being underreported. While the numbers are increasing, governments in developing countries say they have had little choice but to relax what restrictions they put in place because otherwise they would face financial ruin. India lifted its lockdown the same day it saw a record rise in infections. At a time when developing country government budgets are under pressure to deal with the health crisis and its economic consequences, debt payments could be a serious diversion of scarce resources.